Growth and Trend in Area, Production and Yield of Major Crops of Khyber Pakhtunkhwa, Pakistan - Abid, Saleem; Shah, Nisar Ali; Hassan , Abdul; Farooq, Arshad; Masood, M Asif (Asian Journal of Agriculture and Rural Development, 2014)
The present study was conducted with a view to analyzed growth and trend in area, production and yield of major crops of Khyber Pakhtunkhwa. A time series data from 1980-81 to 2011-12 (32 years) of major crops (wheat, maize, rice and sugarcane) were collected. The compound growth rate as well as trend analysis indicated that the area under wheat crop has decreased over the time due to shifting of area to other rabi crops. The production of wheat during 1981-85 to 2010-12 was increased due the corresponding increase in per hectare yield of wheat crop in Khyber Pakhtunkhwa. The results show that area, production and yield of maize was increased over the time the reason is that more area was brought under hybrid and improved open pollinated maize varieties. The area under rice crop has decreased whereas their production increased due the corresponding increase in per hectare yield of rice crop. It was revealed from the results that area, production and yield of sugarcane crop was increasing at a rate of 0.24 percent, 0.85 percent and 0.60 percent per annum, respectively.